Analysis of Business Model Innovation Using Product - Service System Mapping in the Coating Industry - Nanang Alamsyah; Bunga Hardiyana; Mohammad Rachman Waluyo; Wendy Febrianty Mardhiyah (PT ARRUS Intelektual Indonesia, 2026)
This study examines the business model transformation of PT XYZ, an Indonesian coating manufacturer, through Product-Service System (PSS) implementation to enhance competitiveness and create added value in the furniture coating industry. The research employs a qualitative case study approach using PSS questionnaires with Yes/No categorical questions, in-depth interviews with the Plant Manager, non-participant observations, and secondary data from company documents and scientific literature on PSS frameworks. Data were analyzed through PSS Matrix mapping to identify current position, expected future position, and capability-based eligibility across nine PSS quadrants, followed by gap analysis and trade-off assessment to formulate strategic recommendations. The results show that PT XYZ currently operates in Quadrant 4 (Product-Related Software) with a color-detection application as a usage enabler, demonstrating initial transition from conventional product sales toward use-oriented services. Eligibility analysis reveals the company possesses adequate capabilities to enter seven PSS quadrants, supported by expert human resources, financial capacity, and solid business networks. The findings suggest that PT XYZ should strategically focus on three priority quadrants: Quadrant 4 (enhancing digital platforms with integrated technical data and consultation services), Quadrant 5 (developing equipment leasing services with bundling schemes), and Quadrant 8 (implementing outsourcing strategies through professional contractors), enabling gradual transformation from product seller to solution provider that delivers higher functional value and strengthens long-term competitive advantage in saturated global markets.